2008
DOI: 10.1007/s11104-008-9659-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silicon nutrition on cadmium uptake, growth and photosynthesis of rice plants exposed to low-level cadmium

Abstract: The effect of silicon (Si) nutrition on lowlevel cadmium (Cd) toxicity symptoms was investigated in hydroponically-grown rice seedlings (Oryza sativa L.). Silicon (0.0, 0.2, or 0.6 mM) was added when seedlings were 6 or 20 days old representing early (Si E ) or late (Si L ) Si treatment, respectively. Cadmium (0.0 or 2.5 μM) was added when seedlings were 6 days old. Measurements included generation of CO 2 and light response curves; chlorophyll fluorescence analysis; growth; and tissue-element content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(96 citation statements)
references
References 71 publications
12
77
1
1
Order By: Relevance
“…Mitigation effect of Si was determined in maize plants grown at 0.2 mM Zn concentration in nutrient solution (Kaya et al 2009). Consistent data are known for Cd+Si treated rice (Nwugo & Huerta 2008). Similarly, Si improved the growth of maize exposed to Cd (Vaculík et al 2009).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Mitigation effect of Si was determined in maize plants grown at 0.2 mM Zn concentration in nutrient solution (Kaya et al 2009). Consistent data are known for Cd+Si treated rice (Nwugo & Huerta 2008). Similarly, Si improved the growth of maize exposed to Cd (Vaculík et al 2009).…”
Section: Discussionsupporting
confidence: 60%
“…For example, Si plays an important role in increasing the resistance of plants to pathogenic fungi (Fauteux et al 2005;Resende et al 2009). Silicon also mitigates cadmium inhibitory effects in rice and maize plants (Nwugo & Huerta 2008;Vaculík et al 2009). This positive influence also has been recorded in the case of other metals and plant species, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon was also effective in alleviating Cr stress by increasing the concentrations of photosynthetic pigments and the efficiency of chlorophyll fluorescence parameters (Ali et al, 2013). Silicon application increased quantum efficiency of open PS2 centers in a dark-adapted state (Fv/Fm) and photochemical quenching coefficient in a lightadapted state (qP) parameters in rice plants under Cd stress (Nwugo and Huerta, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…He studied the effects Cd stress on seed germination, seeding growth and seed amylase activities in rice, the results showed than Cd stress had bad influence on these indexes [7]. Cd stress also had some influence on enzymes and photosynthesis in growing rice seedlings [8,9]. Wet biomass of T5 and T6 was significantly higher than that of T4 which showed that MB could prevent rice from destroy under Cd stress.…”
Section: Effect Of Different Treatments On Biomassmentioning
confidence: 99%